ACCOUNTING CONTROLS AND SYSTEMS AS KEY DRIVERS OF RELIABLE FINANCIAL REPORTING - Jurayeva Risolat Shukhrat kizi; Mardonov Shakhriyor Kholmirzo ugli (Ecomind Press, 2025)
This article examines the critical role of accounting controls and systems in ensuring the reliability of financial reporting. It highlights how internal control mechanisms, audit processes, and accounting information systems collectively contribute to the accuracy, transparency, and credibility of financial statements. The study analyzes international experiences and scholarly perspectives, demonstrating that effective implementation of accounting controls reduces errors, mitigates fraud risks, and enhances investor confidence. Additionally, the integration of corporate governance practices and compliance with regulatory standards is shown to strengthen the overall reliability of financial reporting. The findings provide both theoretical insights and practical recommendations for organizations aiming to improve their financial reporting quality. This research underscores the strategic importance of accounting mechanisms as key drivers of reliable and transparent financial information.
Keywords: Accounting controls, internal control systems, audit mechanisms, accounting information systems, reliable financial reporting, corporate governance, regulatory compliance, transparency, error reduction, investor confidence.